1988
DOI: 10.1111/j.1151-2916.1988.tb05794.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Silicon Nitride Ceramics in Aqueous Hydrogen Chloride Solutions

Abstract: The leaching behavior of pressureless sintered and hotpressed SiJN4 containing Yz03, A1203, and AlN and hot isostatically pressed SiJN4 without additives was studied in 0.1M to 1OM HCI aqueous solutions at 50" to 100°C. Y and Al ions contained in the grain-boundary phase dissolved in HCI solutions, but dissolution of the Si ion from the matrix was negligible. The dissolution of Y and Al ions in HCI solutions was adequately described by a surface-chemical-reactioncontrolled, shrinking-core model in <1M HCI solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…6) These results showed that the mechanical strength of the corroded Si Q N R ceramic was signi®cantly degraded due to the surface defects formed by the dissolution of the grain boundary phase. In the case of corrosion tests under hydrothermal conditions in water, an oxide ®lm was formed over the surface of the specimen.…”
Section: Introductionmentioning
confidence: 78%
“…6) These results showed that the mechanical strength of the corroded Si Q N R ceramic was signi®cantly degraded due to the surface defects formed by the dissolution of the grain boundary phase. In the case of corrosion tests under hydrothermal conditions in water, an oxide ®lm was formed over the surface of the specimen.…”
Section: Introductionmentioning
confidence: 78%
“…Besides the described zirconia ceramics, several composites are used, with the most prominent being zirconia-toughened alumina containing 10-20 vol% ZrO 2 (ZTA) and alumina-toughened zirconia (ATZ). Y-TZP is widely used in cutting applications and dental implants and hence the hydrothermal stability of this material has been & Yoshimura, 1996;Sato et al, 1988b;Sato, Sato, Tamura, & Okuwaki, 1992;Sato, Tokunaga, Endo, et al, 1988a, 1988bSchilm et al, 2006;Schilm et al, 2007;Schilm, 2004;Schilm, Herrmann, & Michael, 2004a, 2004bSeipel & Nickel, 2003;Sharkawy & El-Aslabi, 1998;Shimada & Sato, 1989 Figure 12 Strengths of different ceramic materials after corrosion in 1 N NaOH, H 2 SO 4 and water at elevated temperatures (temperature is given in the graph) after 200h .…”
Section: Corrosion Of Different Ceramics In Aqueous Solutionsmentioning
confidence: 97%
“…This finding is confirmed by the fact that HIPed Si 3 N 4 ceramic without sintering additives shows very high corrosion resistance. 17 In this case the X-value is approximately four. The nature of the network modifying ions e.g.…”
mentioning
confidence: 90%